Double lethal effects of fusion gene of wild-type p53 and JunB on hepatocellular carcinoma cells - Guo, Cheng; Liu, Qingguang; Zhang, Lei; Yang, Xue; Song, Tao; Yao, Yingmin (Journal of Huazhong University of Science and Technology. Medical sciences, 2012)
Summary This study explored the double lethal effects of pEGFP-C1-wtp53/junB fusion gene on hepatocellular carcinoma (HCC) cells. wtp53/junB fusion gene was constructed and transformed into HepG2 cell line. Expression of KAI1 was detected by quantitative real-time PCR and Western blotting, cells apoptosis rate was detected by flow cytometry, proliferation of cells was detected by MTT chromometry, cell transmigration was detected by using transwell systems. The results showed that after transformation with pEGFP-C1-wtp53/JunB, the expression level of KAI1 protein was up-regulated, being 8.13 times the blank control group in HepG2 cells and significantly higher than 2.87 times which transformed with pEGFP-C1-JunB, 3.11 times which transformed with pEGFP-C1-wtp53 ( P <0.001). Apoptosis rate of HepG2 cells transformed with pEGFP-C1-wtp53/JunB was significantly higher than that of other groups ( P <0.001), and invasive ability of HepG2 cells transformed with pEGFP-C1-wtp53/JunB was significantly lower than other groups ( P <0.001). It was concluded that the fusion gene of wtp53 and JunB could not only inhibit the growth of hepatoma cells and promote tumor cell apoptosis, but also suppress the invasive ability of tumor cells by up-regulating the expression of KAI1.